2020
DOI: 10.3390/f11050534
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Approach for the Identification of Instability in the Wood Using Acoustic Emission Technology

Abstract: In order to monitor the crack growth of the wood material better and reduce failure risks, this paper studied the attenuation characteristics of acoustic emission signals in wood through pencil lead breaking (PLB) tests, in the aim of estimating the true amplitude value of the acoustic emission source signal. The tensile test of the double cantilever beam (DCB) specimens was used to simulate the crack tip growth within wood material, monitoring acoustic activity and location of crack tips within wood material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The investigation showed that the most monitored acoustic Eeission parameters were amplitude (A), energy (E) and counts (C), which were frequently studied against time, crack length and load (even in their cumulative form) with their distribution often highlighted. Among the parameters less frequently studied there are the frequency characteristics [11,[16][17][18][19][20][21], other parameters such as the energy release rate (G) [22], the fracture toughness (K) [23,24], root mean square of the signal voltage (RMS) [25][26][27], density surface energy value (DSV) [16,23], stress (σ), strain (ε) [20,[28][29][30][31][32] and modulus of elasticity (MoE) [32,33].…”
Section: Subject Areas Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation showed that the most monitored acoustic Eeission parameters were amplitude (A), energy (E) and counts (C), which were frequently studied against time, crack length and load (even in their cumulative form) with their distribution often highlighted. Among the parameters less frequently studied there are the frequency characteristics [11,[16][17][18][19][20][21], other parameters such as the energy release rate (G) [22], the fracture toughness (K) [23,24], root mean square of the signal voltage (RMS) [25][26][27], density surface energy value (DSV) [16,23], stress (σ), strain (ε) [20,[28][29][30][31][32] and modulus of elasticity (MoE) [32,33].…”
Section: Subject Areas Of the Researchmentioning
confidence: 99%
“…In Shao et al [39] a theoretical approach was presented in the study of the fractal theory applied to examine the fracture surfaces of five types of woods. In Zhao et al [22], based on thermodynamic approach, a theoretical model for predicting crack instability was established and the model was verified by double cantilever beam (DCB) tests.…”
Section: Subject Areas Of the Researchmentioning
confidence: 99%
“…In this area, a generalized criterion for the maximum energy release rate is known [9]. Energy release in the process of damage and destruction of wood [10] and rocks [11] can be estimated indirectly by recording acoustic emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Load-displacement curves for uniaxial compression of wood [4,26,27] and materials such as sandstone and concrete [18,28] have certain similarities. The similarity of loaddisplacement curves for various indicates that some methods of analyzing rock behavior under load can be adapted to analyze wood failure, subject to certain limitations associated with different material properties [4,22,29]; for example, the acoustic emission analysis mentioned above is an effective support tool for experimental studies of both rock and wood failure [10,11,[29][30][31]. The generalization of experimental data has formed the basis of a number of defining models of the mechanical behavior of wood.…”
Section: Introductionmentioning
confidence: 99%
“…The b-value was originally proposed and used in seismological studies by Gutenberg et al [9] . The b-value is also widely used in the study of rocks because of the similarity between the energy signal released when a rock breaks and the energy signal released by an earthquake [10][11][12][13] . The b-value is often calculated using the maximum likelihood and least square method.…”
Section: Introductionmentioning
confidence: 99%